High Order Thinking Skills pada Buku Teks Bahasa Indonesia SMP Kelas VII Terbitan Kemendikbud - Selvia, Nova; Mukhlis, Muhammad (UIR Press, 2023)
This research aims to analyze the content of High Order Thinking Skills in the Indonesian Language textbook for Junior High School (SMP/MTS) Grade VII published by Kemendikbud. The results of the study show that the textbook has a good amount of HOTS content. This research has positive implications for education, especially in the field of Indonesian Language education. The textbook can be considered as a high-quality learning resource and can be used in schools that have not yet adopted this textbook. The presence of HOTS in the exercises provided in the textbook brings significant benefits to the students, as it helps them develop critical and creative thinking skills. These skills are crucial in facing complex challenges and situations in the future. This research has the potential to serve as a strong foundation for improving the quality and relevance of Indonesian Language textbooks in the future. Thus, this research makes a positive contribution to the development of Indonesian Language education and curriculum enhancement at the Junior High School level (SMP/MTS).